Exercise for Stroke Rehabilitation: A Bibliometric Analysis of Global Research From 2001 to 2021 - Dong, Yulin; Weng, Linman; Hu, Yinhu; Mao, Yuxing; Zhang, Yajuan; Lu, Zefeng; Shi, Tingting; Du, Renren; Wang, Wu; Wang, Jinyan; Wang, Xueqiang (Frontiers in Aging Neuroscience, 2022)
Objective: To make a bibliometric analysis of global trends in research into exercise interventions for stroke between 2001and 2021. Method: this study did the systematic literature from 2001 to 2021 in Web of Science Core Collection . CiteSpace software was used to analyse the relationship of publications with countries, journals, authors, references and keywords. Results: A total of 3484 publications were obtained in the bibliometric analysis. The number of publications increased gradually over the period. The United States have the most number of publications , The journal stroke had the most citations per paper(106.95) and the highest impact factor (IF 2020,7.194). The most high frequency keywords are ‘stroke’, ‘rehabilitation’, and ‘recovery’, the top of burst key words are ‘health’, ‘speed’ and ‘aerobic exercise’. Conclusions: These findings provide the trends of exercise for stroke s and provided the potential research frontiers in the past 20 years. It will be a useful basis for further research into focus issues, cooperators, development trends.